Clinacanthus nutans: a review of the medicinal uses, pharmacology and phytochemistry - Alam, Md Ariful; Ferdosh, Sahena; Ghafoor, Kashif; Hakim, Md Abdul; Juraimi, Abdul Shukor; Khatib, Alfi; Sarker, Md. Zaidul Islam (Elsevier (Singapore) Pte Ltd, 2016)
Clinacanthus nutans Lindau is known as snake grass belonging to the Acanthaceae family. This plant has diverse and potential medicinal uses in traditional herbal medicine for treating skin rashes, insects and snake bites, lesions caused by herpes simplex virus, diabetes, and gout in Malaysia, Indonesia, Thailand and China. Phytochemical investigations documented the varied contents of bioactive compounds from this plant namely flavonoids, glycosides, glycoglycerolipids, cerebrosides and monoacylmonogalatosylglycerol. The pharmacological experiment proved that various types of extracts and pure compounds from this species exhibited a broad range of biological properties such as anti-inflammatory, antiviral, antioxidant, and anti-diabetic activities. The findings of toxicity study showed that extracts from this plant did not show any toxicity thus it can be used as strong therapeutic agents for specific diseased conditions. However, further experiments on chemical components and their mode of action showing biological activities are required to elucidate the complete phytochemical profile and assess to confirm their suitability for future drugs. This review summarizes the medicinal uses, phytochemistry and pharmacology of this plant in order to explore its therapeutic potential and gaps necessitating for prospected research work.